Q: How do you get -2 equals 4r plus s solving for s?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

4r+3 = 3-2 4r = 3-3-2 4r = -2 Divide both sides of the equation by 4 to find the value of r: r = - 1/2

(r + 2)(r + 2)

-2 - 2r or -2(1 - r)

you need 2 equations to solve for 2 variables

Solving by the elimination method: x = 7 and y = 2

Related questions

-2=4r+s s=-4r-2 or s=-(4r+2)

-4r+6=14 isn't an inequality, its a linear equation. Anyway... -4r+6=14 (-6) -4r=8 (/4) -r=2 (x-1) r=-2

4r+3 = 3-2 4r = 3-3-2 4r = -2 Divide both sides of the equation by 4 to find the value of r: r = - 1/2

(r + 2)(r + 2)

-2 - 2r or -2(1 - r)

you need 2 equations to solve for 2 variables

There are 2 unknowns

4r +3 = 3r-2 r + 3=-2 r=-5 basically collect terms so that you get one coefficient of r (in this case 4r on one side and 3r on the other. To get the three r over to the other side you subtract 3r on both sides.) Then r+ 3=-2, so that's simple algebraic manipulation.

Solving by the elimination method: x = 7 and y = 2

Solving by elimination: p = 3 and q = -2

4r + 4 = 5r 4r - r = 3r 4r x r = 4r^2 4r/r = 4

x = 2 or x = 2/5